Determining the impacts of deforestation and corn cultivation on soil quality in tropical acidic red soils using a soil quality index - Wuping Huang (Elsevier, 2021)
Forests around the globe have been converted to agricultural land to meet human demands. The investigation of soil quality index (SQI) as affected by land use change is essential to prevent and control soil degradation mainly in rapidly developing nations. Research on the effects of land-use change on soil quality, especially within deep soil layers, remains lacking despite the prevalence of forest conversion. Here, we selected six paired plots in an intact forest and an adjacent corn field and collected soil samples from 11 layers at depths of 0–140 cm. We then evaluated 16 soil variables for inclusion in a minimum data set and built a SQI from this dataset. Our results indicate that soil organic carbon, total nitrogen, potassium, and free iron are the most important indicators of soil quality in tropical acidic red soils. Deforestation and corn cultivation related to significant decreases in SQI. Of note, SQI decreased to a differing extent among different soil layers, implying that degradation was not constant among layers, despite the fact that tilling typically affects only the top 0–20 cm of soil. The effect of agricultural conversion on soil quality was more pronounced in topsoil soil layers than in the deep layer. The main driver of soil degradation in corn fields was found to be reduced total nitrogen, followed by reduced potassium. Therefore, mitigating or reducing the loss of these nutrients is recommended, possibly through fertilization. We also note that active iron plays an important role in maintaining soil organic carbon concentrations, and thus is critical for maintaining soil quality.